KRIZA MAĐARSKE DEMOKRATIJE U LOKALNOM I GLOBALNOM KONTEKSTU - Dejan Bursac (Srpska Politička Misao)
Book review: Peter Wilkin. 2016. Hungary’s Crisis of Democracy: The Road to Serfdom. London: Lexington Books, p. 223.